Ocular safety profile and intraocular pharmacokinetics of an antagonist of EphB4/EphrinB2 signalling. Issue 12 (7th October 2010) - Brar, Manpreet; Cheng, Lingyun; Yuson, Ritchie; Mojana, Francesca; Freeman, William R; Gill, Parkash S
Abstract : Aims: To characterise the ocular safety profile of sEphB4 and its pharmacokinetics in rabbit eyes. Methods: 15 rabbits with single intravitreal injection of sEphB4 in the right eye (1000 μg, 465 μg, 160 μg or 80 μg) and phosphate-buffered saline in the left eye were studied at different time points by monitoring inflammatory changes, intraocular pressure, electroretinogram and histological changes. The dose of 80 μg/eye was injected intravitreally into 21 rabbits, and the fellow eyes were used as controls for sEphB4 ocular pharmacokinetics. sEphB4 concentrations were measured in the vitreous, retina, choroids and plasma using ELISA at the designated time points. Results: The study showed that there was no evidence of intraocular toxicity at any time point with any dose tested. No statistically significant differences were seen in the intraocular pressure, scotopic and photopic ERGs, and histopathology between the control and sEphB4 injected eyes. A pharmacokinetic study demonstrated a vitreous half-life of 4.1 days and 6.3 days in the retina. The mean residence time of the drug was 10.45 days in the retina and 7.95 days in the choroid. Conclusion: It seems that sEphB4 at the concentrations studied did not appear to be toxic to rabbit eyes and may be a longer-acting treatment option to the current therapies for ocular abnormal neovascularisation.